TEACHERS' STRATEGIES IN IMPLEMENTING RELIGIOUS MODERATION CONTENT IN THEMATIC LEARNING AT AL-AZHAR MADRASAH IBTIDAIYYAH AND MAS MADAIYYAH SENDURO - Ahmad Hafidz Lubis; Afandi Afandi; Artamin Hairit (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to describe teachers' strategies in implementing religious moderation in thematic learning at Al-Azhar Madrasah Ibtidaiyyah (MI) and Madaiyyah Senduro Madrasah Aliyah (MAS). Religious moderation, as a balanced, tolerant, anti-violent, and nation-oriented religious attitude, is very important to be instilled from an early age through formal education. This study uses a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, classroom observations, and documentation studies, then analysed using the interactive analysis model of Miles, Huberman, and Saldana. The results showed that teachers at MI Al-Azhar used concrete experience-based strategies, such as storytelling, collaborative games, and daily prayer habits, to instil the values of tolerance and togetherness. Meanwhile, teachers at MAS Madaiyyah developed strategies for thematic discussions, case studies, and self-reflection that encourage students to think critically and reflect on religious moderation. The obstacles encountered include teachers' limited understanding of religious moderation, a dense curriculum, and the negative influence of social media. However, supporting factors such as madrasah policies, teacher role models, and the local socio-cultural context contributed to the success of the implementation. This study emphasises the importance of the role of teachers as agents of moderation through thematic learning, as well as the need to strengthen teacher capacity and learning innovation to shape a moderate generation in an era of diversity.